The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s41983-023-00613-x
|View full text |Cite
|
Sign up to set email alerts
|

Reasons withholding intravenous thrombolysis for acute ischemic stroke in an Indonesian Tertiary Center

Abstract: Background Intravenous thrombolysis is the current therapy of choice in patients with acute ischemic stroke (AIS). While highly effective, the rate at which the procedure is employed is low. Studies evaluating the causes withholding thrombolytic treatment in developing nations remain scarce. We aim to determine the factors withholding thrombolytic treatment in AIS patients. Methods This is a retrospective study of AIS patients at Siloam Hospitals L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Corroborating a Brazilian study, carried out in the South of the country, which obtained a median time of 1.3h (0.76h to 2.26h). 16 Nonetheless, it was different in international studies, such as one held in Indonesia, where the median was 45 minutes, 29 and in another developed in Lebanon, where 32.9% underwent a CT scan in less than 20 minutes. 14…”
Section: Discussionmentioning
confidence: 94%
“…Corroborating a Brazilian study, carried out in the South of the country, which obtained a median time of 1.3h (0.76h to 2.26h). 16 Nonetheless, it was different in international studies, such as one held in Indonesia, where the median was 45 minutes, 29 and in another developed in Lebanon, where 32.9% underwent a CT scan in less than 20 minutes. 14…”
Section: Discussionmentioning
confidence: 94%
“…It is widely recognized that the earlier the intravenous thrombolysis is administered, the better the outcome is [18]. While intravenous thrombolysis remains underutilized globally, the rate of intravenous thrombolysis in Indonesia is still very low, ranging between 0.5% and 6.9% compared to a study in Italy that showed a much higher intravenous thrombolysis rate of 24.4% [7,[19][20][21]. Other than the delayed presentation, several factors also contributed to the rate of intravenous thrombolysis, including spontaneous clinical improvement, minor stroke, patient/family refusal, extensive infarction, seizures at onset, and history of gastrointestinal bleeding and/or acute bleeding diathesis [20,22,23].…”
Section: Discussionmentioning
confidence: 99%